Selective CD28 blockade impacts T cell differentiation during homeostatic reconstitution following lymphodepletion - Habib, Jakob G.; Liu, Danya; Crepeau, Rebecca M.; Wagener, Maylene E.; Ford, Mandy L. (Frontiers in Immunology, 2023)
Introduction Costimulation blockade targeting the CD28 pathway provides improved long-term renal allograft survival compared to calcineurin inhibitors but may be limited as CTLA-4-Ig (abatacept, belatacept) blocks both CD28 costimulation and CTLA-4 coinhibition. Directly targeting CD28 while leaving CTLA-4 intact may provide a mechanistic advantage. Fc-silent non-crosslinking CD28 antagonizing domain antibodies (dAb) are currently in clinical trials for renal transplantation. Given the current standard of care in renal transplantation at most US centers, it is likely that lymphodepletion via thymoglobulin induction therapy could be used in patients treated with CD28 antagonists. Thus, we investigated the impact of T cell depletion (TCD) on T cell phenotype following homeostatic reconstitution in a murine model of skin transplantation treated with anti-CD28dAb. Methods Skin from BALB/cJ donors was grafted onto C56BL/6 recipients which were treated with or without 0.2mg anti-CD4 and 10μg anti-CD8 one day prior to transplant and with or without 100μg anti-CD28dAb on days 0, 2, 4, 6, and weekly thereafter. Mice were euthanized six weeks post-transplant and lymphoid cells were analyzed by flow cytometry. Results Anti-CD28dAb reversed lymphopenia-induced differentiation of memory CD4+ T cells in the spleen and lymph node compared to TCD alone. Mice treated with TCD+anti-CD28dAb exhibited significantly improved skin graft survival compared to anti-CD28dAb alone, which was also improved compared to no treatment. In addition, the expression of CD69 was reduced on CD4+ and CD8+ T cells in the spleen and lymph node from mice that received TCD+anti-CD28dAb compared to TCD alone. While a reduced frequency of CD4+FoxP3+ T cells was observed in anti-CD28dAb treated mice relative to untreated controls, this was balanced by an increased frequency of CD8+Foxp3+ T cells that was observed in the blood and kidney of mice given TCD+anti-CD28dAb compared to TCD alone. Discussion These data demonstrate that CD28 signaling impacts the differentiation of both CD4+ and CD8+ T cells during homeostatic reconstitution following lymphodepletion, resulting in a shift towards fewer activated memory T cells and more CD8+FoxP3+ T cells, a profile that may underpin the observed prolongation in allograft survival.